Comparison of the generation of α-glucosidase inhibitory peptides derived from prolamins of raw and cooked foxtail millet: In vitro activity, de novo sequencing, and in silico docking. (15th June 2023) - Fu, Yongxia; Liu, Zhenyu; Wang, Han; Zhang, Fan; Guo, Shang; Shen, Qun
Highlights: Prolamin hydrolysates of raw and cooked foxtail millet inhibited α-glucosidase. Cooked millet prolamin hydrolysate < 3 kDa (PCFMH<3 ) better inhibited α-glucosidase. The ratio of peptides with good α-glucosidase binding force was higher in PCFMH<3 . Cooking increased the production of peptides with good anti-α-glucosidase effects. AMFLPGA, TMMMLLP, FFLPQ, and FMLPQ could be potent inhibitors of α-glucosidase. Abstract: Foxtail millet prolamin has been demonstrated to have anti-diabetic effects. In this study, we compared the generation of anti-α-glucosidase peptides derived from prolamins of raw and cooked foxtail millet (PRFM and PCFM). PRFM and PCFM hydrolysates (PRFMH and PCFMH) both exhibited α-glucosidase inhibitory activity. After ultrafiltration according to molecular weight (Mw), the fraction with Mw < 3 kDa in PCFMH (PCFMH<3 ) showed higher α-glucosidase inhibitory activity than that in PRFMH (PRFMH<3 ). The composition of α-glucosidase inhibitory peptides identified by de novo sequencing in PCFMH<3 and PRFMH<3 was compared by virtual screening, combining biological activity, net charge, grand average of hydropathicity (GRAVY), and key hydrophobic amino acids (Met, Pro, Phe, and Leu). We found that the proportion of peptides with excellent α-glucosidase binding force in PCFMH<3 was higher than in PRFMH<3 . Overall, cooking may positively affect the generation of peptides that perform well in inhibiting α-glucosidase derived from foxtail millet prolamin.